Policy Model For Sustainable Ecotourism Development In The Capital Of The Indonesian Archipelago Based On Local Community Empowerment - Aullia Vivi Yulianingrum; Fajar Alam; Aidul Fitriciada Azhari; Insan Tajali Nur (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The potential of natural caves spread across Sanggulan Village, Sebulu District, Kutai Kartanegara Regency, East Kalimantan Province, which is a buffer zone for the capital of the Indonesian archipelago, has great potential to be developed as a tourism and educational facility. Currently, ecotourism development is widespread in the IKN area to fulfill the smart city slogan which prioritizes aspects of nature conservation, social, cultural and economic empowerment of local communities as well as learning and educational facilities. These elements significantly influence traditions, socio-economic life of the community and the empowerment of local village products. The village's identity is summarized in a slogan that highlights the richness of natural resources, preservation of cultural heritage and IKN's ecotourism priorities. By using a policy model that is Meaningful Participation, Asset Based Community Development (ABCD) and SWOT analysis of Regional Government policies in regulating or making regulations regarding cave or karst ecotourism, the aim is to increase IKN tourism by integrating cultural, geotourism and legal aspects. This model promotes participatory legal regulation, empowerment of local communities and environmental conservation to encourage sustainable regional development.